Topological optimization of cementitious binders: Advances and challenges. (August 2019) - Liu, Han; Du, Tao; Krishnan, N.M. Anoop; Li, Hui; Bauchy, Mathieu
Abstract: The properties of cementitious binders are controlled by their structure at different scales. However, the complexity of their disordered structure makes it challenging to elucidate the linkages between atomic and mesoscale structure and macroscopic properties. Recently, topological approaches—which capture the connectivity of the atoms or grains while filtering out less relevant structural details—have been shown to offer a powerful framework to guide the optimization of cementitious binders' properties by tuning their internal topology at different scales. Here, we review recent advances in the topological optimization of cementitious binders at the atomic and mesoscopic scales and attempt to identify the present challenges that need to be overcome. Elucidating the topological genome of cementitious binders (i.e., how their macroscopic properties are encoded in their topology) could accelerate the optimization of existing binders or discovery of novel formations with unusual properties.